Performance Analysis of Energy Efficient Clustering Protocol in WSN - Rana, A; Bala, M; Varsha (International Journal of Computer Sciences and Engineering, 2025)
Over the past decades, clustering is the main issue in the wireless sensor network. To make the clustering and cluster head selection is the main issue in the wireless sensor network. In this study, the authors propose and evaluate the performance of MSEEC (Multi level stable and energy efficient clustering protocol) protocol in heterogeneous wireless sensor network based upon the parameters number of alive nodes, dead nodes , packet transferred and average Total energy and also makes the network better by using the hybrid ACO-PSO (Ant-colony optimization-particle swarm optimization) optimization technique for cluster head selection in MSEEC protocol on the parameters packet transferred and alive nodes.